Balancing sustainability and commerce in international negotiation: the EU and its fisheries partnership agreements. Issue 1 (2nd January 2017) - Zimmermann, Hubert
ABSTRACT: Since the 1980s, the European Union (EU) has negotiated fisheries agreements with numerous maritime countries. These agreements stipulate the conditions under which the European fishing industry gains access to foreign territorial waters. In the past two decades, the EU also wants to advance development objectives and promote environmental sustainability with these agreements. Not surprisingly, EU negotiators have found it hard to accommodate these often contradictory preferences. I argue that a mushrooming institutional structure of EU decision-making in the negotiation and ratification of fisheries agreements makes it increasingly hard for concentrated commercial interests to influence the outcome of the negotiations. As a result, diffuse interests representing a dominant normative discourse of social and ecological responsibility increasingly dominate the aggregation of preferences. I also find that the Commission (and its allies in the Council) benefit from the heterogeneity of diverse lobbies to pursue their geopolitical goals, again privileging the non-commercial dimensions of these agreements.